1987
DOI: 10.1177/073490418700500502
|View full text |Cite
|
Sign up to set email alerts
|

Risk Oriented Evaluation of Fire Gas Toxicity Based on Laboratory Scale Experiments- The DIN 53436 Method

Abstract: Small scale laboratory tests are described which show that the DIN 53436 method is applicable to studying smouldering processes as well as flaming fires with respect to fire atmospheres generated. This is shown by the temperature build up and the concentration of CO2 and CO versus time. In order to obtain a uniform combustion with fast burning samples too a modified protocol was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The large variety of feasible experimental configurations, of sample amounts which may be employed, and of analytical techniques which may be integrated for the characterization of products formed in experimental runs, led to a widespread use of FBRs in experimental investigations related to the study of products generated in thermal decomposition processes (Einbrodt, Hupfeld, Prager, & Sand, 1984;Prager, Einbrodt, Hupfeld, Mueller, & Sand, 1987). Fig.…”
Section: Analysis Of Gaseous and High Molecular Weight Products By Fimentioning
confidence: 99%
“…The large variety of feasible experimental configurations, of sample amounts which may be employed, and of analytical techniques which may be integrated for the characterization of products formed in experimental runs, led to a widespread use of FBRs in experimental investigations related to the study of products generated in thermal decomposition processes (Einbrodt, Hupfeld, Prager, & Sand, 1984;Prager, Einbrodt, Hupfeld, Mueller, & Sand, 1987). Fig.…”
Section: Analysis Of Gaseous and High Molecular Weight Products By Fimentioning
confidence: 99%
“…This is equivalent to 2500 ppm/cm2 and 4583 ppm/cm2 of CO2, respectively. Prager and colleagues [18] found that combustion of a sample of spruce wood with a total surface area of 5.9 cm2 under flaming combustion conditions produced 51,000 to 55,000 ppm CO2. These tests were done using a 5 L/min carrier gas flow.…”
Section: Co and C02 Productionmentioning
confidence: 99%
“…The tubular furnace of DIN 53436 enables one to simulate a self-sustained smoldering process by varying the test parameters as described elsewhere [31].…”
Section: Smoldering Firementioning
confidence: 99%
“…Taking into account the mass or volume of the exposed material, as well as the secondary air stream, one can get material-specific data. With the DIN tube system the timetemperature relationship can be simulated for different fire scenarios, as described elsewhere [30,31].…”
Section: Dynamic Systemsmentioning
confidence: 99%